Factors Associated with Nurses’ Performance at Mitra Medika General Hospital Pangkalpinang - Nurmiati, Nurmiati; Maryana, Maryana; Fitri, Nurwijaya (Genius Journal, 2026)
Introduction: Hospitals are complex healthcare organizations where leadership and work motivation play crucial roles in influencing nurse performance and the overall quality of healthcare services. Objective: Nurses' performance is one of the key indicators in determining the quality of health services in hospitals. Optimal performance is influenced by several factors, including leadership style, work motivation, and work environment. This study aims to determine the relationship between leadership style, work motivation, and work environment with nurses’ performance at Mitra Medika General Hospital Pangkalpinang in 2025. Method: This research used an analytical quantitative approach with a cross-sectional design. The sample consisted of 50 respondents selected using total sampling technique. The research instrument was a questionnaire, and data were analyzed using the Chi-Square test. Result: The results of the study indicate that there is no significant relationship between leadership style, work motivation, and work environment with nurses' performance at Mitra Medika General Hospital Pangkalpinang in 2025. The significance values for each variable are p = 0.603 for both leadership style, p = 0,323 for work motivation, and p = 0.953 for work environment, all of which exceed the 0.05 threshold. The conclusion of this study is that leadership style, work motivation, and work environment do not have a significant relationship with nurses' performance. Conclusion: The results of this study are expected to serve as a consideration for future researchers to develop further studies with broader variables and a qualitative approach, for educational institutions to utilize the findings as applied learning material, and for healthcare institutions to pay attention to leadership style, work motivation, and work environment in order to support the improvement of nurses' performance.